Designing A Concept To Facilitate The Setup Of African University Presses - Havemann, Jo (My University, 2023)
A virtual presentation about opportunities and approaches to set up new as well as leverage existing University Presses in Africa. By invitation from the Harare Institute of Technology; https://www.hit.ac.zw/. Mentioned resources include: Association of University Presses; https://aupresses.org/ JISC New University Press Toolkit; https://www.jisc.ac.uk/guides/new-university-press-toolkit AfricArXiv country profiles: https://africarxiv.pubpub.org/countries-of-africa Zimbabwe country profile: https://africarxiv.pubpub.org/zimbabwe
Keywords: University Press; Institutional Repository; Research in Africa